Pengaruh Kombinasi Air Leri dan Limbah Cair Tempe Terhadap Hasil Jamur Merang (Volvariella volvaceae) - Maulana, Muhammad Rival; Sugiono, Darso; Rahmi, Hayatul (JURNAL AGROPLASMA, 2023)
Straw mushroom is one of the agricultural commodities that has a good future for breeding. The increase in public consumption of straw mushroom in Indonesia is not proportional to the amount of production. This research aims to get the best combination treatment of leri water and tempe liquid waste in increasing the yield of straw mushroom (Volvariella volvaceae). This research was conducted in Pasirmulya Village, Majalaya District, Karawang Regency from August to September 2020. This research used an experimental method with a single-factor Randomized Block Desaign (RBD) consisting of 8 treatments, namely K0 (without leri water and tempe liquid waste), K1 (leri water 25%), K2 (leri water 50%), K3 (leri water 100%), K4 (tempe liquid waste 50%), K5 (tempe liquid waste 100%), K6 (leri water 50% and tempe liquid waste 50%), and K7 (25% leri water and 50% tempe liquid waste). Each treatment is repeated 3 times. The results showed that the combination of leri water and tempe liquid waste had a significant effect on the fruit body diameter and the fruit body weight. K6 treatment (50% leri water and 50% tempe liquid waste) gave the highest yield of fruit body diameter (12,82 mm) and K1 treatment (25% leri water) gave the highest result in fruit body weight (9,21 g)